Direct nanoscale observations of CO2 sequestration during brucite [Mg(OH)2] dissolution - Hövelmann, J.; Putnis, Christine; Ruiz-Agudo, E.; Austrheim, H. (2012)
The dissolution and carbonation of brucite on (001) cleavage surfaces was investigated in a series of in situ and ex situ atomic force microscopy (AFM) experiments at varying pH (2-12), temperature (23-40 °C), aqueous NaHCO 3 concentration (10-5-1 M), and PCO2 (0-1 atm). Dissolution rates increased with decreasing pH and increasing NaHCO3 concentration. Simultaneously with dissolution of brucite, the growth of a Mg-carbonate phase (probably dypingite) was directly observed. In NaHCO 3 solutions (pH 7.2-9.3,), precipitation of Mg-carbonates was limited. Enhanced precipitation was, however, observed in acidified NaHCO 3 solutions (pH 5, DIC ˜ 25.5 mM) and in solutions that were equilibrated under a CO2 atmosphere (pH 4, DIC ˜ 25.2 mM). Nucleation predominantly occurred in areas of high dissolution such as deep step edges suggesting that the carbonation reaction is locally diffusion-transport controlled. More extensive particle growth was also observed after ex situ experiments lasting for several hours. This AFM study contributes to an improved understanding of the mechanism of aqueous brucite carbonation at low temperature and pressure conditions and has implications for carbonation reactions in general. © 2012 American Chemical Society.